Effect of perioperative desmopressin in cats with mammary carcinoma treated with bilateral mastectomy. (11th August 2020) - Wood, Christopher J.; Chu, Margaret L.; Selmic, Laura E.; Mayhew, Philipp D.; Holt, David E.; Martano, Marina; Séguin, Bernard; Singh, Ameet; Boston, Sarah E.; Lux, Cassie; Liptak, Julius M.
Abstract: Perioperative administration of desmopressin has shown to significantly decrease rates of local recurrence and metastasis, and increase survival times in dogs with grade II and III mammary carcinomas. The objective of this study was to compare the oncologic outcome of cats with mammary carcinoma treated with bilateral mastectomy with or without perioperative administration of desmopressin. Medical records from nine veterinary institutions were searched to identify cats diagnosed with mammary carcinoma treated with bilateral mastectomy. Sixty cats treated with single‐session or staged bilateral mastectomy were included. There were no significant differences in oncologic outcomes found between cats treated and not treated with desmopressin. No adverse effects were seen in any of the cats treated with perioperative desmopressin. Postoperative complications occurred in 18 cats (38.3%) treated with single‐session bilateral mastectomy and in three cats (23.1%) treated with staged bilateral mastectomy ( P = .48). Histologic grade and a modification of a proposed five‐stage histologic staging system were both prognostic for disease‐free interval. Incomplete histologic excision was associated with significantly increased rates of metastasis and tumour progression, and a shorter median survival time (MST). Cats that developed local recurrence also had a significantly shorter MST. The results of this study do not support the use of perioperative desmopressin to improve outcome when performing bilateral mastectomy for the treatment of mammary carcinoma in cats.